The significance of glass stud gems in insular metalwork, 7th to 9th century - Gleeson, Jennifer M. (Trinity College (Dublin, Ireland). Department of History of Art and Architecture, 2006)
Decorative glass studs appear extensively on high status insular metalwork between the seventh and twelfth centuries. Their importance is signified by the use of precious materials, attention to minute detail and prominent position on high status artefacts. Two of the most important pieces of Irish Early Christian art, the Ardagh chalice and the Derrynaflan paten display forty-two and fifty-four embellished glass studs respectively. Glass studs are unique to Irish art and record the interpretation by Irish workshops of external technical and stylistic influences in art. Due to the extensive nature of the topic it has been necessary to curb the subject to one that could be dealt with within the constraints of this dissertation. With this in mind the questions have been restricted to a period between the seventh and early ninth century. By limiting itself to this period of time the study will examine the emergence of the earliest glass studs and the development of glass and metal working skills to the highest levels achieved on examples such as the eighth century Ardagh chalice, 'Tara' brooch and Derrynaflan paten. Studs are made from amber, quartz crystal, gold, silver, bronze, millefiori glass, enamel and coloured glass. Many studs, as found on the Derrynaflan chalice and 'Tara' brooch, are made from amber, while two separate artefacts, display studs of quartz crystal. These have been excluded from the study because they are naturally occurring gems and while polished and shaped by craftsmen, they do not require the same technical knowledge needed to manipulate glass and glass- metal composites. However they will be referred to when the treatment or artefact ...
Keywords: History of Art, M.Phil; M.Phil Trinity College Dublin, 2006